(untitled) (Balneo and PRM Research Journal, 2024)
Background: Cerebral palsy is a non-progressive neurodevelopmental condition that results in varied degrees of disability, with upper limb functioning affected in over 80% of cases. The objective of this study was to investigate the impact of passive movement training of the hand (PMT) with robot-assisted therapy (RAT) compared to PMT with functional electrical stimulation (FES). Methods: Fifty-eight patients diagnosed with CP, aged between 7 and 14 years, participated in a two-week rehabilitation program involving physical therapy (PT) combined with either RAT or FES. We assessed the evolution of cylinder grip, fingers extension, pinch grips, lateral grip, and three-point grip in each therapy group post-rehabilitation to determine the more effective passive movement training. Results: Both the RAT group (p < 0.001) and the FES group (p < 0.01) demonstrated a statistically significant improvement in all parameters. Patients who received PT and FES exhibited greater improvement in each movement, except for the pinch index grip, where the RAT group showed superior results. Conclusions: Our findings indicate positive effects of both PMTs on hand function rehabilitation. We recommend incorporating both therapies into rehabilitation programs for enhanced outcomes.